Вы находитесь на странице: 1из 8

, .

I)

f ( x ) A .

A < 0 ,
A = 0 , f ( x) = 0
A > 0 , f ( x)

f ( x) A

f ( x) A
II)

f ( x ) <A .

< 0 ,

A
A = 0 ,
A > 0 ,

f ( x ) <A

A < 0 ,

A > 0 ,

f ( x ) >A .

< 0 ,

f ( x) 0

x D( f )

A > 0 ,

f ( x) > A

f ( x) > A

g ( x ) = 0 , .
g ( x ) > 0 , f ( x )

g ( x ) = 0 ,

( f ( x)

g ( x) )

f ( x ) >g ( x )

f ( x) 0

x D ( f )

x D( g )

g ( x ) > 0 ,

f ( x ) > g ( x )

f ( x) > g ( x)

f ( x ) <g ( x )

g ( x ) = 0 ,
g ( x ) > 0 ,

g ( x) )

f ( x ) g ( x )

( f ( x)
( f ( x)

g ( x) )

f ( x ) g ( x )

f ( x ) g ( x)
f ( x ) g ( x )

IX) f ( x ) g ( x ) f ( x ) g ( x )
.
f ( x ) g ( x )

f 2 ( x ) g 2 ( x)

f ( x ) g ( x )

f ( x) g 2 ( x)
2

X) ( ).

V) f ( x ) <g ( x )
.
g ( x ) < 0 , .

f ( x) > A

f ( x) < A

f ( x) g ( x)

f ( x) g ( x)

VIII) f ( x ) g ( x )
.
g ( x ) < 0 , f ( x ) g ( x )

f ( x)
A = 0 ,

f ( x ) g ( x )

f ( x ) A

f ( x) A
f ( x ) A

IV)

f ( x ) g ( x )

VII) f ( x ) >g ( x )
.
g ( x ) < 0 , f ( x ) >g ( x )

f ( x ) A .

f ( x)
A = 0 ,
f ( x)

f ( x) < A

f ( x) > A
III)

g ( x ) = 0 ,
f ( x ) = 0
g ( x ) > 0 ,

<g ( x )

f ( x) < g ( x )

f ( x) > g ( x)

VI) f ( x ) g ( x )
.
g ( x ) < 0 , .

P.S
.

, .
I) f ( x ) = A,
.
A < 0 , .

A = 0 ,
f ( x) = 0
A > 0 ,

A R

f ( x ) =A
f ( x ) =A

f ( x) = A
f ( x ) =A

II)
.
1

f ( x ) =g ( x )

f ( x ) =g ( x )

g ( x) 0

f ( x) = g ( x)
g ( x) 0

f ( x) = g ( x)

f ( x ) =g ( x )

f ( x) 0

f ( x) = g ( x)
f ( x) 0

f ( x) = g ( x)

III) f ( x ) = g ( x )
.
1
f ( x ) = g ( x )

f 2 ( x) = g 2 ( x)
2

f ( x ) = g ( x )

f ( x ) =g ( x )
f ( x ) =g ( x )

IV) f ( x ) =f ( x ) f ( x ) = f ( x )
.
f ( x ) =f ( x )

f ( x) 0

f ( x ) = f ( x )

f ( x) 0

f ( x ) < g ( x)

I)
.
g ( x )

f ( x) = 0

g ( x)

f ( x ) g ( x ) < 0

VIII)
.

f ( x ) g ( x ) < 0 .

f ( x ) g ( x)

.
g ( x )

f ( x ) g ( x) 0

f ( x) > 0

g ( x) 0

f ( x) 0

g ( x ) 0

f ( x) < g 2 ( x)

< 0 , .
g ( x ) 0 ,

.
.

0 , .
g ( x ) > 0 , f ( x ) < g ( x )

II)

f ( x ) g ( x ) 0

VII)

f ( x ) g ( x)

f ( x) 0

g ( x ) 0

f ( x) g 2 ( x)

f ( x) > 0

g ( x) < 0
IX)

f ( x) 3 g ( x)

f ( x) 3 g ( x)
f ( x ) g ( x)
3

f ( x ) > g ( x)

III)
.

f ( x ) > g ( x)

g ( x) 0

2
f
(
x
)
>
g
( x)

f ( x) 0

g ( x) < 0

f ( x ) g ( x)

IV)
.

X)

f ( x ) g ( x)

V)

f ( x) 0

g ( x) < 0

f ( x ) g ( x ) 0

XI)

f ( x ) 3 g ( x) 3 ( x )

.
3

f ( x ) 3 g ( x) 3 ( x )

f ( x) g ( x) 0

.
I) (
) ( ).
II)

f ( x ) = g ( x)

f ( x) > 0

g ( x) 0

VI)

f ( x ) g ( x ) > 0

f ( x) > 0

g ( x) > 0

f ( x ) g ( x ) > 0 .

f ( x ) = g ( x)

f ( x) = 0

g ( x)

f ( x) g ( x) ( f ( x) + g ( x)) 0

g ( x) 0

2
f
(
x
)

g
( x)

f ( x) + 3 g ( x) 3 f ( x) + g ( x)

f ( x) + 3 g ( x) 3 f ( x) + g ( x)

III)

g ( x) 0

2
f ( x) = g ( x )

f ( x ) g ( x ) = 0

.
,
, ,
.

f ( x) = 0

g ( x) ( )
g ( x) = 0

f ( x) 0
f ( x) =

IV)

g ( x )

f ( x) =

g ( x)

f ( x) = g ( x)

f ( x) 0
f ( x) = g ( x)

g ( x) 0

f ( x)

V)

g ( x ) = 0

f ( x)

g ( x ) = 0

f ( x) = 0

g ( x) 0
VI)

g ( x) = 0

f ( x) 0

f ( x) + 3 g ( x) =V ( x)

.
3

f ( x) + 3 g ( x) =V ( x)

f ( x ) + 3 3 f 2 ( x ) g ( x ) + 3 3 f ( x ) g 2 ( x ) + g ( x ) =V 3 ( x )

f ( x) + g ( x) + 3 3 f ( x) g ( x)

f ( x) + 3 g ( x) = V 3 ( x)

(1)

V ( x)
f ( x ) + g ( x) + 3

f ( x ) g ( x) V ( x) = V 3 ( x )

(2)
1 2 , ,
.
VII)

f ( x) + 3 g ( x) = 3 f ( x) + g ( x)

f ( x) + 3 g ( x) = 3 f ( x) + g ( x)

f ( x) = 0

f ; g
f ( x) + g ( x) = 0

f ; g

g ( x) = 0

f ; g

VIII)

a f ( x ) + n b + f ( x) = g ( x)

.
n

a f ( x) + n b + f ( x) = g ( x)

n a f ( x) = U 0

n b + f ( x) = V 0

log ( x ) f ( x ) > 0

f ( x) > 0
( x) > 0

( x) 1
( f ( x ) 1) ( ( x ) 1) > 0

U + V = g ( x)
n n
U + V = a + b
IX)

f ( x ) +a

f ( x) =b

.
,

,
. ( )
X)

ax + b + k cx + d a1 x + b1 + p cx + d = A

ax + b + k cx + d a1 x + b1 + p cx + d = A
.

cx +d = y 0

cx + d = y 2

x=

y2 d
c

y2 d
y2 d
a
+ b + ky a1
+ b1 + py = A
c
c
, ,
.

f ( f ( x )) = x .
y > f (x) - ,
f ( f ( x )) = x - .

XI)
.

f ( x) > 0
( )
log ( x ) f ( x ) log ( x ) y( xx) <>00
( x ) 1

y( x ) > 0
( x ) > 0

3) log
( x () x) f1( x ) > 0
.

) 1()x() yf( (xx) )>1)log


( (x( x) ) 11) > 0
( xlog
log ( x) (ff( (xx) )>01) (

1+ 1+ x =x

( x) > 0
( x) < 1

I .
f ( x) > 0
f ( x ) < 1

- .

1+ x =x

x x 1 = 0

1+ 5
1 5
; x2 =
2
2
3+ 5

x=
2
x1 =

XII)
.
.

( x +1) 2 + 2 3 ( x 1) 2 = 3 3 x 2 1

x +1 = U , x 1 = V
U + 2V 2 3UV + 0

I.

II.
III.
IV.

.
1)
.

( x) > 0

II . ( x ) > 1

f ( x) > 1

1)

1 + x = x 1

f ( x) = x

log ( x ) f ( x ) log ( x ) y ( x ) < 0

2)

log ( x ) f ( x ) > 0

V.

f ( x)

g( x)

f ( x) 0

f ( x) = 1
g ( x) = k ( x)

f ( x)

g( x)

= f ( x)

= f ( x)

k( x)

k( x)

f ( x ) =1 .
f ( x ) = 0 .
f ( x ) = 1 .

f ( x) < 0

f ( x) 1
g ( x) = k ( x)

(a + b )

1)
.

a b

f ( x)

= k

(a + b )(a b ) =1 , (a b ) = (a +1 b ) ,

(a + b ) ( )
f x

f ( x)

(a + b )

. a +

f ( x)

f ( x)

=k

= y , y

1
=k
y

.
I) .

a 0 x n + a1 x n 1 + a 2 x n 2 + ... + a n 1 x + a n = 0

, ..

a0 = a n , a1 = a n 1 ,

a 2 = a n 2

1) .

2x + 9x x + 9x + 2 = 0
x = 0 - ,
x 2 0 .
9 2
2x 2 + 9x 1 + + 2 = 0
x x
1
1
2( x 2 + 2 ) + 9( x + ) 1 = 0
x
x
1
1
: x +
= y , x2 + 2 = y2 2
x
x
4

..

a +b = c +d
( x a )( x b)

x = 1
6
5
4
x + x 6x 7 x3 6x 2 + x + 1 = 0
. x = 0 -

x3 +

x3 0
6 1 1
x3 + x 2 6x 7 + + 2 + 3 = 0
x x
x
1
1
1
( x 3 + 3 ) + ( x 2 + 2 ) 6( x + ) 7 = 0
x
x
x
1
1

x+ = y,
x2 + 2 = y2 2 ,
x
x

1
= y3 3y
x3

II) ax 4

+ bx 3 + cx 2 + dx + l = 0 ,

a b2
=
l d2

.
III) .
1.
2

x 4
x 2
x +2
5
=0
44
+12 2
x
+
1
x

1
x 1

x 2
=U
x +1
5U 2 44V 2 + 12UV = 0

1)

x +2
=V
x 1

V = 0 , U = 0 ,

2)

VI)

( ax 2 + b1 x + c)(ax 2 + b2 x + c) = kx 2

x2 0

.
I) .
,
.

a0 sin n x + a1 sin n 1 x cos x + a 2 sin n 2 x cos 2 x + ... + a n 1 sin x c


a 0 ; a1 ; a 2 ;...; a n

- .

3 sin x + 4 cos x = 5, x

x
x
+ 4 cos 2 = 5 1
2
2
x
x
x
x
x
x
6 sin cos + 4 cos 2 4 sin 2 = 5 sin 2 + 5 cos 2
2
2
2
2
2
2
x
x
x
x
9 sin 2 6 sin cos + cos 2 = 0
2
2
2
2
x
x
cos
= 0 , sin = 0 ,
2
2
x
, cos
0 .
2
x
x
2 x
cos
0 , : 9tg 2 6tg +1 = 0
2
2
2
3 sin 2

a cos x + b sin x = c
c = 0 , .
2) c 0 a 2 + b 2 0 ( a
b 0), a 2 + b 2 ,
1)

cos x +

a2 + b2

b
a2 + b2

,
.

U
U
5 +12 44 = 0
V
V

x 1

a
a +b
2

sin x =

2
2
a +b

2.

5x
5 x
x
x +
=6
x +1
x + 1

II)

V = 0

U = 0

V 0
2

Ax
Bx
+ 2
=k
ax + b1 x + c ax + b2 x + c
2

,
.

( x c )( x d ) , .

VII)

( x + 1)( x + x 6 x 7 x 6 x + x + 1) = 0
5

( x a ) n + ( x b) n = k
a +b
y = x
2

a )( x b)( x c)( x d ) = k

V)

x + 2 x 5 x 13 x 13 x 5 x + 2 x + 1 = 0
x = 1 - .
6

UV = 6

U + V = 5

IV) ( x

2) .

, .
1
7

5x
5x
=U , x +
= V , UV = 6
x +1
x +1
5x
5x
U + V = x
+x+
=5
x +1
x +1
x

a +b
2


b
+

2
2
a +b

= sin ;

1;

a2 + b2
b
a +b 2
2

= 1 ,

b
a + b2
2

= cos ,

sin cos x + cos sin x =


c

sin ( x + ) =
) ,

) ,

a2 + b2

c
a +b 2
2

>1 . .

a 2 + b 2 < c 2 , .

1 . .

a 2 + b 2 c 2 ,

c
a 2 +b 2

x + = ( 1) arcsin
k

x = arcsin

a + b2
2

a + b2
2

+ k , k

+ ( 1) arcsin

a +b
2

a + b2
2

+ k , k

III)
.
sin x cos x; sin x cos x = 0

sin x cos x = y , ( sin x cos x ) 2 = y 2 ,

1 2 sin x cos x = y 2 , 2 sin x cos x = y 2 1